Program I'datut Ta'lim Kurikulum Al-Azhar Kairo Mesir - Rodiansyah, Wahyu; Zulpikri, Zulpikri (Universitas Indraprasta PGRI Jakarta, 2024)
SMAS IT Diniyyah Al-Azhar Jambi applies an international curriculum in the religious field, namely the Al-Azhar Cairo Egypt curriculum which focuses on Islamic religious subjects, Arabic and Tahfidz. Every textbook uses Arabic as the language of instruction. This research is experimental research with the aim of finding out the effect of the i'datut ta'lim program in increasing the Arabic language scores of class Diniyyah Al-azhar Jambi has 96 students. Researchers used data collection techniques in the form of tests. This research uses a prerequisite test before carrying out hypothesis testing, namely a normality test with the help of SPSS 25 which is proven to be all normal data with a significance value of less than 0.05 and a homogeneity test with the help of SPSS 25 which is proven to be all homogeneous data with a significance value of less than 0.05 . The results of this research indicate that the I'datu ta'lim program can improve the Arabic language scores of class X SMAS IT Diniyyah Al-azhar Jambi.